Safe drinking water and sanitary facilities utilization in households of Belagavi urban slums, Karnataka, India - Vasanthakumar, Jambulingam; Gajula, Bhuvana; Ganta, Shilpa Reddy (International Journal Of Community Medicine And Public Health, 2020)
Background: Safe water and adequate sanitation are basic to the health of every person, yet many people throughout the world do not have access to these needs. Access to these basic services is not only a fundamental right, but also a steppingstone to sustainable development of the country. Objective of this study was conducted to measure the proportion of slum households using improved drinking water and sanitation facilities. Methods: Study was conducted among 620 slum households in Belagavi from by interviewing one member from each household using WHO/UNICEF joint monitoring program core questions on drinking water and sanitation for household surveys. Results: All the slum households (100%) used improved drinking water source; piped water in yard or plot (68.22%) being the primary source. 94.35% of households used improved water source for cooking and/or hand washing purpose. 49.03% of households used improved sanitation facilities and 55.97% used unimproved sanitation facilities. Proportion of households with no latrine facilities and practicing open defecation were 13.06%. About 27.69% households had reported diarrheal events in children in the previous month. Type of latrine used by households was found significantly associated with the diarrheal events in children. Conclusions: Utilization of safe drinking water in Belagavi slums has increased when compared to global and national levels but households with piped water supply are still low. Access to improved sanitation facilities is still lacking in many households. Increasing access to basic sanitation at the household level and behavior change awareness programs could help in achieving universal sanitation coverage.